Carbonic anhydrase IX, an endogenous hypoxia marker, expression in head and neck squamous cell carcinoma and its relationship to hypoxia, necrosis, and microvessel density. - Beasley, N; Wykoff, C; Watson, P; Leek, R; Turley, H; Gatter, K; Pastorek, J; Cox, G; Ratcliffe, P; Harris, A (2001)
Carbonic anhydrase IX (CA IX) is a transmembrane glycoprotein with an active extracellular enzyme site. We have shown previously that it was hypoxia inducible and may therefore be an endogenous marker of hypoxia. It is overexpressed in some tumors, particularly renal cell carcinoma. The aim of this study was to examine the expression and localization of CA IX in head and neck squamous cell carcinoma (HNSCC) and relate this to the location of tumor microvessels, angiogenesis, necrosis, and stage. Expression of CA IX was determined by immunoblotting in three HNSCC cell lines grown in normoxia and hypoxia (pO(2) 0.1%) and three paired tumor and normal tissue samples of HNSCC. Archived paraffin sections (79) of HNSCC were immunostained with antibodies to CA IX and CD34 to determine microvessel density (MVD). By double staining sections with CA IX and CD34, the distance between blood vessels and the start of CA IX expression and necrosis was calculated. CA IX was induced by hypoxia in all three HNSCC cell lines and overexpressed in HNSCC tumor tissue. Overexpression was localized to the perinecrotic area of the tumor on immunostaining, and the percentage area of the tumor expressing CA IX was significantly higher with more tumor necrosis (P = 0.001), a high MVD (P = 0.02), and advanced stage (P = 0.033) on univariate analysis and necrosis (P = 0.0003) and MVD (P = 0.0019) on multivariate analysis. The median distance between a blood vessel and the start of CA IX expression was 80 microm (range, 40-140 microm). CA IX is overexpressed in HNSCC because of hypoxia and is a potential biomarker for hypoxia in this tumor. Overexpression may help to maintain the intracellular pH, giving tumor cells a survival advantage and enhancing resistance to radiotherapy and chemotherapy. CA IX is a potential target for future therapy in HNSCC.